Penerapan Keselamatan dan Kesehatan Kerja (K3) Pada Keamanan Kinerja Karyawan PT. Indofood - Edy Soesanto; Novia Hanifah Rahma; Alfia Dwi Cahyani; Muhamad Ramdan (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Modern and outdated technologies must be used to produce any product that can be sold on the open market in today's industrial age. The use of more complex work tools will increase the potential for bottlenecks and have a negative impact on employee performance. Protection and fulfillment of occupational safety and health (K3) is the single most important factor affecting the ability of employees to do their jobs. PT Indofood CBP Sukses Makmur Tbk is a company engaged in the food and beverage processing sector which was founded in 1971. Protection and fulfillment of occupational safety and health (K3) is one of the factors that affect employee performance. The purpose of this study is to find out how the implementation of K3 in the performance security of employees of PT Indofood CBP Sukses Makmur Tbk. The research method used is qualitative research with a descriptive approach. The results of this study are that PT Indofood CBP Sukses Makmur Tbk has carried out OSH well as a safety measure for employee performance from potential hazards in the company.